PEDAGOGICAL CONDITIONS FOR THE DEVELOPMENT OF STUDENT REFLECTIVENESS IN THE EDUCATIONAL PROCESS - Murtоzaeva Makhfuza Murtozaevna (Journals Park Publishing, 2025)
In this article, the authors sought to consistently introduce secondary school students to the truths of the past (history) and express scientific thoughts about the development of reflective skills based on the development of objective thinking within History classes. The results of the survey are also described in order to ensure the effectiveness of the research.
Keywords: Education, school, pupils (learners), History, lesson, past, thinking, development, reflective.